Zinc removal in biofilm reactor with support media - Rahaiminullah, Razali (2009)
Zinc removal in biofilm reactor with support media by mixed culture, attract a lot of interest from the public and as well as chemical industry. In this research, biofilm process was selected as a treatment method with using sequencing batchreactor (SBR).This method is better choice when compared in cost of treatment. Atthe beginning of the experiment, the mixed culture was collected from the drain and acclimatized in 10 litres reactor and the growth of mixed cultured is monitored by take suspended solid test. The mixed culture is acclimatized within two months by feed trace amount of glucose and 1mg/L of zinc. The hydraulic retention time (HRT) selected for this research is 5 days. Three parameters were chosen during run theexperiment which was suspended solid (SS) test for monitoring mixed culture growth while chemical oxygen demand (COD) removal and zinc removal for measure the water quality. This research will carry out by controlling the loading rate. The loading rate is choosing from 3 mg/L.d to 5 mg/L.d. The trend of results was determined. Based on result, increasing the loading rate make the all value of parameters decreased. The average value of SS in acclimatize reactor is 2645.39 mg/L. For the treatment reactor, the highest average value of SS is 566.21 mg/L. For COD removal and zinc removal, the highest average was at loading rate 3mg/L.d which is 41.49% and 75.01% respectively. Using Design-Expert programmed, the optimized data obtained. From the Design-Expert data, the zinc removal is 74.38% and the COD removal is 47.73%. The desirability of the lowest parameter of loading rate is 0.81.